The Correlation Between Age And Parity Of Pregnant Women In III Trimester And The Incidence Of Anemia In Pregnancy At The Nd Clinic. Retno, Kabanjahe District, Karo District, 2023 - Silalahi, Imelda Sarwani Br; Eva Ratna Dewi; Sinuhaji, Lidya Natalia Br.; Sembiring, Adelina; Manik, Nursinta; Rahmah (Department of Midwifery, Faculty of Nursing and Midwifery, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2023)
Pregnancy anemia is where the hemoglobin level is less than 11 grams or less than 33% at any time during the first trimester of pregnancy. Keywords: Pregnant women's class, pregnancy, anxiety, primigravida. Research objectives: To determine the relationship between age and parity of pregnant women in the third trimester and the incidence of anemia in pregnancy at the Nd Clinic. Retno, Kabanjahe sub-district, Karo district in 2023. This research design uses a descriptive research design with a cross-sectional quantitative approach.This research was carried out in April-July 2023. The research population was all pregnant women who visited and were hospitalized at the Nd Clinic. Retno, Kabanjahe District, Karo Regency, namely 43 people. The sampling technique was purposive sampling. The sample in this study was 43 people. Bivariate analysis was carried out on two variables that were thought to be related (Notoatmodjo: 2012). The statistical tests used in this research are the Chi Square test (x2) and the Fisher's Exact Test. This test is used because the data to be analyzed is categorical data. To see the significance of the statistical calculation results, a significance limit of α=0.05 is used so that if statistical analysis results are found with a p value <0.05, the relationship between the two variables is declared meaningful or significant. especially those who suffer from anemia, so that they know how their HB levels are progressing to normal. Future researchers need to carry out further research in order to develop knowledge, especially about anemia in pregnant women.